STRATEGY FOR INCREASING THE EFFICIENCY OF PILGRIMAGE TOURISM BASED ON MARKETING RESEARCH (The Conference Hub, 2025)
This thesis examines the strategy for increasing the effectiveness of pilgrimage tourism based on marketing research. It highlights the need to radically improve the system of providing tourism services to increase tourism potential, measures to further increase the potential of domestic and foreign tourism, the need to develop a comprehensive action plan to address the main problems in the tourism sector, and other issues.